Aplicativo VISME como estrategia didáctica de enseñanza y aprendizaje de Biología Animal con estudiantes de cuarto semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Arévalo Peñaranda, Jonathan Ismael (2024)
ICT have been of great help in education, since they have created favorable environments where the interaction of the teacher and students in the study of animal biology is allowed, but, the problem arose because in the career of Pedagogy of Experimental Sciences, Chemistry and Biology, even unconventional ways were used when teaching, such as slides, clippings from books or magazines, leaving aside the use of teaching guides based on digital resources, generating the use of digital resources: Chemistry and Biology, even unconventional ways were used when teaching, such as slides, clippings from books or magazines, leaving aside the use of didactic guides based on digital resources, generating little interest and little meaningful learning, That is why the present research had the objective of applying the didactic guide "A GLANCE AT ANIMAL LIFE" in the subject of Animal Biology to contribute to the teaching and learning of vertebrates in fourth semester students, being devised through the constructivist methodology of the inverted classroom, by means of the application "Visme". The research methodology corresponds to a quantitative approach, non-experimental design, according to its type and scope: descriptive, according to the objective: basic, according to the place: field and bibliographic. To collect the data, a survey was applied with its instrument, the 10-question questionnaire applied to the 32 students enrolled in the fourth semester of the course. It was concluded that the didactic guide with "Visme" was excellent, since it awakened interest in the subject, generating significant learning for those who took the course on vertebrates, so it is recommended to implement the didactic guide "A GLANCE AT ANIMAL LIFE" to facilitate the teaching and learning process of animal biology in students.